The Effect of Motivation on the Tendency to Quit: A Field Study - Aydin Durak (GoAcademica Research & Publishing, 2020)
There are many factors that motivate employees in organizations. In the presence of these factors, the employee's performance and thus production increases. In addition, as a result of the lack of motivation, many consequences result in negative consequences. One of these consequences is quitting the job. In other words, it can be said that individuals who are not motivated will leave their jobs over time. It can be stated that the person who is motivated towards his / her job and environment in the place of work will depend on his / her job and will not think of leaving his / her job. Considering the time and cost of employing employees, it is an important issue that managers show the necessary sensitivity to the concept of motivation. Thus, it can be said that there is a correlation between the level of motivation and the tendency to quit. In this study, the effect of motivation on the tendency to quit was examined and a conceptual framework was formed by first researching the literature on the subject. Later, the field study was explained and the findings obtained were presented through tables and interpreted and the results reached were evaluated.